EXECUTIVE INFORMATION SYSTEM ON STOCK TRADING IN JAKARTA ISLAMIC INDEX (JII) : Executive Information System - Indah Firliyani; Karin Sukma Dhiana; Zerlinda Zsa Zsa Zabrina; Suryo Budi Santoso (Universitas Islam Lamongan, 2023)
This study will examine the effect of executive information systems on stock price trading in the Jakarta Islamic Index (JII). Testing this research using library research techniques (Library Research) which is descriptive. Which in this study uses supporting data from previous studies. The results of the study show that the executive information system (SIE) has a significant effect on the trading price of share listed on the Jakarta Islamic Index (JII).